PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII SMP NEGERI 2 KOTA JAMBI - Rismaya Oktaviani; Harman Harman; Sri Dewi (Universitas Batanghari Jambi, 2018)
Abstract: This research is motivated by low students' critical thinking ability. This is caused by the ineffectiveness of learning in the classroom in the learning process with conventional model while the students who receive it more passive and afraid to express the assumption because they think that math is hard to learn. So teachers need to apply a fun learning system and more real in improving the ability to think critically by using Realistic Mathematics Education Approach (RME) to help critical thinking of students to be more critical. This research is an experimental research. The population in this research is all students of class VII SMPN 2 Kota Jambi Academic Year 2017/2018. Sampling using Random Sampling technique, which is taken class VII A and VII D where two classes are given different treatment. This study aims to determine the difference of Realistic Mathematics Education (RME) approach to critical thinking skills of the seventh grade students of SMPN 2 Kota Jambi, the subject of the set. Based on Post-test results can be seen that the critical thinking ability of students of class VIIIA (experiment) SMP Negeri 2 Kota Jambi on the set material, the average value is 76.84 with standard deviation 6.96 whereas in class VIIID (Control) average of 72.75 with standard deviation of 11.64. Based on these calculations there is a difference between the experimental class and the control class, this is the influence of the approach of Realistic Mathematics Edication (RME).Keywords: Realistic Mathematics Education (RME) Approach, Student Critical Thinking Ability